Laminar flow forced convection in ducts : a source book for compact heat exchanger analytical data - Shah, R. K. (Ramesh K.); London, A. L. (Alexander Louis) (Advances in heat transfer. Supplement, 1978)
Laminar Flow Forced Convection in Ducts is a sourcebook for compact heat exchanger analytical data. This book describes the analytical solutions for laminar fluid flow and forced convection heat transfer in circular and noncircular pipes, including applicable differential equations and boundary conditions involving velocity and temperature problems of fluid flow. The book also discusses fluid flow-how much power is required to pump fluids through the heat exchanger, as well as the heat transfer-the determination of q" distribution, and the temperature of fluid and walls. The text also analyzes the coolant or heat transfer fluid flows in a nuclear power reactor composed of a bundle of circular section fuel rods located inside a round tube. R.A. Axford addresses fluid flow and heat transfers results for the rod bundle geometry in "Heat Transfer in Rod Bundles." The book also provides an overview and guidelines that can be used for the designer and the applied mathematician. This book is suitable for engineers working in electronics, aerospace, instrumentation, and biomechanics that use cooling or heating exchanges or solar collection systems